Fatal choriocarcinoma syndrome suspected of being an ectopic pregnancy - Ibrahim Z.A.; Lung W.S.; Shamsir Aris; Shamugam P.S.; Ti V.K. (Mary Ann Liebert Inc., 2024)
Background: Choriocarcinoma is an aggressive, rapidly invasive, and widely metastasizing epithelial malignancy. It may arise from previously normal or abnormal pregnancy. Choriocarcinoma occurrence in a Fallopian tube is a rare event. Case: A 34-year-old para 8+2, woman presented with right iliac fossa pain of 1 day's duration. According to a urine test, she appeared to be pregnant again. Ultrasonography showed a left adnexal mass, but her uterine cavity was empty and she was diagnosed as having an ectopic pregnancy. Intraoperatively, the left broad ligament and infundibulopelvic ligament were dilated and engorged. A left salpingectomy and wedge resection of the broad ligament were performed. Serial preoperative ?-human chorionic gonadotropin (?-hCG) level testing during admission increased markedly within 2 days (15,000-752,601 milli-international units [mIU)/mL]). Her postoperative ?-hCG level was significantly reduced (225,000 mIU)/mL). A chest radiograph was performed because, preoperatively, she had respiratory distress that was treated as an infection. The radiograph showed bilateral basilar consolidation. She appeared to be recovering well postoperatively but sudden respiratory distress on the ninth postoperative day caused her to collapse, and she died. Results: A postmortem examination revealed that this patient had succumbed to choriocarcinoma syndrome as a result of lung metastasis from a Fallopian tube choriocarcinoma. Conclusions: Albeit its rarity, choriocarcinoma should be considered as one of the possible differential diagnoses of a tubal mass in a patient with an elevated ?-hCG level. Early detection is crucial in view of the good prognosis even at an an advanced stage of the disease. (J GYNECOL SURG 30:152) Copyright 2014, Mary Ann Liebert, Inc. 2014.